THE CRISIS OF DEMOCRACY: AN EMPIRICAL ASSESSMENT OF SUDAN AFTER THE FALL OF OMAR BASHIR - Muhammad Hasan Izzurrahman; Yon Machmudi (Arabic Literature Department, 2024)
Sudan's democratic journey continues to face a long and steep road. The stepping down of President Omar Bashir in 2019 has brought the country to a condition that is increasingly far from the requirements of democracy. This research offers theoretical and empirical assessments to answer whether Sudan has experienced a democratic crisis. Through a socio-historical approach, this research will operationalize Brigitte Weiffen's concept of democratic crisis and apply it to the condition of Sudan. The research method used is qualitative and aims to explain the phenomenon of democracy in Sudan. The data analyzed comes from the author's investigations and notes conducted in the 2018-2020 period at the research location, books, journals, humanitarian agency reports, podcasts, and news. The results show that Sudan is facing a severe democracy crisis. Sudan has fulfilled all three main categories of crisis causes: democratic crisis, disharmony in the civilian coalition, weak legitimacy of the transitional government, and failure to form a government. In addition, the military and paramilitaries are present as challenger actors who continue to intervene and seek to overthrow or fundamentally change the rules of democratic governance.